Teenagers and bodybuilding from the aesthetic, fitness and recreation perspectives - sahsahi, mahdi; djoubar, merrouane; benbouza, hichem (sports creativity, 2025)
Adolescents nowadays suffer from a lot of emptiness and find it very difficult to spend these times. On the other hand, there is another group of adolescents who see recreational activities, especially of a physical and athletic nature, as the only outlet to spend the extra amount of energy that if not properly exploited may affect them and Their personal lives are negative. And through our field observation of the reality of practicing bodybuilding sport among adolescents, we found that there is a great demand for this category to practice this type of sport, even at the expense of other recreational sports activities, despite their abundance and diversity. The thing that made us study this phenomenon and make a field visit to a number of gymnasiums in order to get a closer look at the reasons for this category heading to this type of sport and what are the goals and objectives of that.